Inter-regional pattern of urbanization in southern Ghana in the first decade of the new millennium. (June 2016) - Stow, Douglas A.; Weeks, John R.; Shih, Hsiao-chien; Coulter, Lloyd L.; Johnson, Harry; Tsai, Yu-Hsin; Kerr, Andrew; Benza, Magdalena; Mensah, Foster
Abstract: We analyze amounts and spatial patterns of land cover and land use change (LCLUC) and particularly change to Built for four contiguous regions of southern Ghana between 2000 and 2010. Our objective is to understand the degree of urban expansion relative to urban densification during this time frame, to understand the relationship between population growth and LCLUC at the census district level, and to explain the patterns of New Built LCLUC throughout this study area. During the study period 1.5% of the study area transitioned to Built, an increase of 56% Built area since 2000, while population increased by 33%. Most (84% of total study area) of this change to Built involved conversion from Agriculture al land use and occurred predominantly in suburban and periurban areas zones of the Accra and Kumasi metropolitan areas. While total population and amount of Built LCLU variables co-vary strongly at the census district level at the beginning and end of the study period, change in population and Built are less strongly correlated. In fact, we observe that new Built development increased at a greater rate than population growth within peri-urban areas of Accra and Kumasi, frequently occurring as spaced residential land use composed of large houses with minimal urban infrastructure. Highlights: From 2000 to 2010 1.5% of land area in southern Ghana converted to Built (56% relative increase). Most new Built occurred in peri-urban areas of Accra and Kumasi, replacing Agriculture. Residential urbanization appears to be leading population growth in peri-urban areas.